Heart Rhythm Disturbances in Cardiac Surgery Patients with Coronary Artery Disease - Gogayeva, Olena K. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To analyze arrhythmological complications in cardiac surgery patients with coronary artery disease (CAD). Materials and methods. This was a retrospective data analysis of 354 cardiac surgery patients with various forms of CAD who were operated on and discharged from the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. The mean age of the patients was 61.9 ± 9.6 years. All the patients underwent laboratory examinations, electrocardiography, echocardiography, coronary angiography and cardiac surgery. The patients with uncomplicated forms of CAD (n = 194) underwent isolated surgical revascularization of the myocardium, in the case of complicated forms of CAD (n = 160), coronary bypass surgery was supplemented with valvular or ventricular correction. Results. Postoperative atrial fibrillation (AF) occurred in 40 (20.6%) patients with uncomplicated CAD and 43 patients with complicated CAD (26.8%), p = 0.1667. Among patients with complicated forms of CAD, 2 (1.25%) had paroxysms of ventricular tachycardia, which required the implantation of a cardioverter-defibrillator, also in this group of patients complete left bundle branch block occurred more often (p = 0.0020). The postoperative period in patients with impaired glucose metabolism was characterized by more frequent development of AF in patients with type 2 diabetes mellitus (33.3%, p = 0.0006), with impaired glucose tolerance (24.8%, p = 0.0156) compared to patients with normoglycemia (12.6%). Conclusions. There was no statistically significant difference in the frequency of postoperative AF in patients with various forms of CAD (p = 0.1667). In the occurrence of postoperative AF paroxysms, the negative influence of type 2 diabetes mellitus (p = 0.0006), impaired glucose tolerance (p = 0.0156), stage III-IV chronic kidney disease (p = 0.0015) and gouty arthritis (p = 0.0072) has been proven. The presence of postoperative AF was associated with acute encephalopathy (p = 0.0291) and panic attacks (p = 0.0043). The occurrence of postoperative AF increased the length of stay of cardiac surgery patients with CAD in the hospital from 8.2 ± 2.9 to 11.06 ± 6.8 days (p < 0.0001).